Management of central venous catheters in pediatric onco-hematology using 0.9% sodium chloride and positive-pressure-valve needleless connector. - Buchini, Sara; Scarsini, Sara; Montico, Marcella; Buzzetti, Roberto; Ronfani, Luca; Decorti, Cinzia (Eur J Oncol Nurs, 2014)
PURPOSE: To describe, in a sample of pediatric onco-hematological patients, the rate of occlusions in unused central venous catheters (CVC) flushed once a week with a 0.9% sodium chloride solution through a positive-pressure-valve needleless connector. METHOD: Retrospective cohort study. Subjects aged 0-17 years were identified through a manual search in medical and nursing records and were observed for two years or until the occurrence of one of the following events: start or resume of continuous infusion; CVC removal; death. The primary study outcome was the frequency of CVC occlusion (partial or complete). RESULTS: Fifty-one patients were identified (median age 6 years). The median duration of follow-up was 169 days (IQR 111-305). During the follow up period, 14 patients (27%) had one CVC occlusion, in 2 cases (4%) the occlusion was complete, in 12 (23%) partial. All the occlusions were solved without the need for catheter removal. The lumen diameter ≤ 4.2 vs > 4.2 French showed a statistically significant association with occlusion at multivariate analysis (OR 4.0; 95% CI 1.1-14.7). CONCLUSIONS: Our findings are reassuring with respect to the management of the CVC using the adopted protocol. The study provides useful information for patient care, by verifying the performance of the adopted CVC management protocol and by identifying critical areas for nursing care.
Keywords: Adolescent; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Child, Preschool; Cohort Studies; Equipment Design; Female; Hematology; Humans; Infant; Infant, Newborn; Italy; Male; Oncology Nursing; Pediatric Nursing; Practice Guidelines as Topic; Retrospective Studies; Sodium Chloride